Modifikasi Minuman Fungsional ‘Keloja’ Berbasis Bahan Pangan Lokal sebagai Makanan Tambahan pada Anak Usia 24-59 Bulan - Iskari Ngadiarti; Muntikah Muntikah; Betty Yosephin Simanjutak (Politeknik Kesehatan Tanjung Karang, 2021)
One solution to overcome the problem of malnutrition in Indonesia is to provide nutritional interventions by adding micronutrient supplementation to food or beverages. This study aims to develop functional drinks from local food (Moringa leaves, tolo beans, and corn) as additional food ingredients for children aged 2-5 years. The first stage of the research carried out tolo bean germination, while in the second stage the study determined the formulation of a local food-based functional drink with four levels of treatment, namely 0% (T1), 5% (T2), 7.5% (T3), 10% (T4). ) Moringa leaves to total formula drinks. Organoleptic tests were carried out by 30 somewhat trained panelists from level 2 students of the DIII and DIV Nutrition study programs. Formulations that were acceptable to the panelists were the T2 formulation with a composition of 50% corn, 50% tolo beans, 5% Moringa leaves, 5% powdered milk, and 10% granulated sugar. The nutritional value of the tolo bean-based functional drink (T2) is 245,95kcal of energy, 8,57gr of protein, 5,25gr of fat, and 41,1 gr of carbohydrates, and 458,71ppm of phenol content per 250ml. With the addition of 5%, Moringa leaves it produces color, aroma, taste, consistency, and acceptance that is most liked by panelists and resembles a drink without the addition of Moringa leaves. It is necessary to carry out further studies related to microbiological tests on functional drinks made from local food so that they can meet the applicable SNI.